Solos carbonáticos desenvolvidos a partir de rochas da Formação Jucurutu no Seridó potiguar - Azevedo, Ana Lívia Araújo (2023)
In pedogenesis, we must pay attention to all the formation factors, but in a semi-arid environment, the dry climate makes the source material the most active formation agent. Temperature and rainfall, combined with the nature of the parent material, are decisive in these conditions. The area covered by this study is part of the lithostratigraphic unit of the Jucurutu Formation, which has Precambrian metamorphic rocks, the highlight of which is the marble that provides the foundation for the formation of carbonate soils. These, in turn, are formed through processes of calcium carbonate accumulation, typical of regions with a hot, dry climate. Some orders of soils can be derived from marble, such as Luvissolos, Chernossolos and Cambissolos. Therefore, the aim of this study is to describe the morphological, physical and chemical characteristics of a soil profile in the municipality of Caicó/RN, in an attempt to highlight the existence of carbonate soils in the Jucurutu Formation. The profile sampled shows characteristics such as a carbonate and hypocarbonate character, as well as a calcic horizon, with calcium carbonate contents of over 800 g kg-1, a chromic character, an argilluvic character, a high Ca2+ reserve, high base saturation and an alkaline pH, thus showing the occurrence of a luvissolic Carbonate Cambissolo Háplico. The work makes a significant contribution to soil science in Rio Grande do Sul by identifying and documenting the existence of these soils previously undocumented in the Seridó region.